Enhancing Competitive Edge: Green Commerce and Digital Marketing Implementation in Supply Chain Industry - Mukhlis, Iqbal Ramadhani (Universitas Dinamika, 2024)
Green business or sustainable business includes sustainable operational activities, using environmentally friendly materials, producing minimal waste products, managing labor sustainably, and responsible delivery methods. The goal of sustainable business is to eliminate negative impacts on the environment, both on a local and global scale. PT. Abaka Supply Chain is a company operating in the supply chain sector in Indonesia which has long been dedicated to providing the best solutions in renewable fuels. This company is known for its commitment to environmentally friendly business with the production of Biomass Wood Pellets. The application of Green Commerce is the main focus in research, with a focus on environmentally friendly practices that can be implemented in industrial supply chains. This research is included in the applied research category because it uses a qualitative descriptive analysis methodology to provide practical findings that are relevant to digital marketing. Additionally, the Digital Marketing aspect involves implementing online marketing strategies, optimizing social media, and how to approach the market efficiently through digital platforms. Integrating Green Commerce and Digital Marketing can provide valuable insight, as well as being an important milestone in advancing the industry towards a more sustainable and highly competitive future.